Numerical Simulation of Single-Mode 3D Rayleigh-Taylor Instability - Dongyung Kim (Modelling and Simulation in Engineering)
Rayleigh-Taylor instability (RTI) is analyzed theoretically by Taylor, and 2-dimensional experimental results are obtained by Lewis in 1950. Over the 72 years, several experiments and theories are developed with the shock-driven Ritchmyer-Meshkov instability (RMI) and the shear-driven Kelvin-Helmholtz instability (KHI). Here, we emphasize the single-mode Rayleigh-Taylor instability (RTI) mixing simulation with a surface area in 3 dimensions. The simulation uses concentration equations and nonzero transport. We observed chaotic interface behavior even for this single-mode simulation, in the sense that the interface appears to have an area proportional to Δx−1, with respect to its mesh (non)convergence (i.e., rate of divergence) properties.